Seatbelt use among bus passengers in Ghana: observed versus self-reported measures. Issue 3 (1st September 2022) - Okyere, Paul; Agyei-Baffour, P.; Harris, M. J.; Mock, C.; Yankson, I. K.; Donkor, P.; Owusu-Dabo, E.
Abstract: Many road traffic injuries in low- and middle-income countries (LMICs) are to bus passengers. We sought to determine the availability, functionality, and observed vs. self-reported use of seatbelts in large intercity buses in Ghana. We observed seatbelt use for 1, 184 passengers in 35 large intercity buses. We interviewed a separate group of 633 bus passengers. All buses observed had seatbelts and most (92.6%) were functional. A little over a fifth (21.6%) of passengers were observed to wear seatbelts. However, 34.5% of passengers in the self-reported survey indicated always wearing seatbelts when riding in buses. Passengers on 5 buses out of the 35 observed where the driver verbally prompted them to wear seatbelts were more likely (57.8%) to wear seatbelts than on the other buses (15.3%, p  = 0.001). Comparing the self-reported survey with observations, passengers tended to overinflate seatbelt use by a factor of 1.6. This study provides useful information for efforts to increase and monitor seatbelt use among large intercity bus passengers in LMICs. Supplemental data for this article is available online at